2011
DOI: 10.1007/s10531-011-0144-7
|View full text |Cite
|
Sign up to set email alerts
|

Bat colony size reduction coincides with clear-fell harvest operations and high rates of roost loss in plantation forest

Abstract: Clear-fell harvest of forest concerns many wildlife biologists because of loss of vital resources such as roosts or nests, and effects on population viability. However, actual impact has not been quantified. Using New Zealand long-tailed bats (Chalinolobus tuberculatus) as a model species we investigated impacts of clear-fell logging on bats in plantation forest. C. tuberculatus roost within the oldest stands in plantation forest so it was likely roost availability would decrease as harvest operations occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 47 publications
0
25
1
Order By: Relevance
“…There is a surprising lack of European studies on the effects of any logging strategy on bats and the only study found for this review which directly related Borkin et al 2011).…”
Section: Loggingmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a surprising lack of European studies on the effects of any logging strategy on bats and the only study found for this review which directly related Borkin et al 2011).…”
Section: Loggingmentioning
confidence: 99%
“…Males selected edges with open unplanted areas within their home ranges, which females avoided, instead selecting older stands for foraging. Borkin et al (2011) also documented the response to the clear-fell harvest of a pine plantation and found a pattern of declining numbers of roosts used, as well as smaller roosting areas and colony sizes. Over 3 years, 21 % of known roosts were lost with 15 % due to forestry operations and 6 % due to natural tree fall.…”
Section: Plantationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current theories include bats being attracted to the turbines (due to the turbines, or their locations on ridge-tops, attracting insects or because of the ultrasound they produce), their placement along the migratory pathways of bats or because bats may perceive towers as potential roost trees (Kunz et al 2007a). When combined with other negative anthropogenic effects on bats, such as habitat modification or clearance and disease, losses caused by wind turbines could negatively impact long-term population trends (Blehert et al 2009;Borkin et al 2011).…”
Section: Editorialmentioning
confidence: 99%
“…Within plantation forest long-tailed bats select home ranges that have higher proportions of near-harvest age stands and within these home ranges choose roosts in stands closest to harvest age [12], [13]. Colonies of C. tuberculatus roosting in mature Pinus radiata adjacent to recently clear-felled areas have significantly fewer bats than those where harvest has not recently occurred [5]. It is suspected that this is due to bats either being killed during harvest operations or moving to other roosting areas.…”
Section: Introductionmentioning
confidence: 99%